Innovations in investments and corporate finance - Makhija, Anil K.; Hirschey, Mark; John, Kose (Advances in financial economics ;, 2002)
This volume focuses on recent pricing puzzles in investments. The valuation of Internet companies, effects of firm size in takeover studies, and long-run performance of mergers in the telecommunications industry are all seen as riddles for the Efficient Markets Hypothesis. Explanations may be found in studies of the effects of differences in investor risk/return preferences, information and liquidity. Also featured are studies describing recent innovations in corporate finance, such as an experimental study of discount rates, an analysis of issues related to the estimation of internal cash flows, corporate payout policy, and the use of convertible and warrant bonds by Japanese firms.